KOMPARASI METODOLOGI HUKUM ALIRAN MAQASIDI DAN ALIRAN SYAKLI - Qotadah, Hudzaifah Achmad (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract: Islamic thought has been developing whenever so there are various streams within the legal methodology especially within the fiqh approach which emerged from the Sahabat era such as fiqh 'Abdullah Ibn Mas'ud, fiqh Umar, fiqh Ibn Umar, etc and therefore the differences between the Companions has given rise to different tendencies of thought between each other both those belonging to the ahl athar or ahl ra'i groups. The obvious difference is that the tendency of thinking based on maqasidi is colored by ijtihad Umar while the tendency of thinking supported syakli (formalism) is more clearly seen within the fiqh of Abdullah Ibn Umar and these streams are created within supported the legal references employed by every group in order to do Istinbath al-hukm. So, a Fuqaha who always looks at the objectives of Islamic Sharia in conducting legal terminology is spoken as Maqasidi while jurists who always look to the form or format in legal rest are spoken as Syakli. Therefore, during this study, the author is inspired to check and analyze the thoughts of the jurists towards legal methodology supported the flow of maqasidi and also syakli.Abstrak: Pemikiran Islam terus berkembang pada setiap masanya, sehingga telah muncul berbagai macam aliran dalam bidang metodologi hukum, utamanya dalam pendekatan fiqh. Perbedaan tersebut muncul sejak masa Sahabat r.a, seperti ‘Abdullah Ibn Mas’ud, fiqh Umar, fiqh Ibn Umar dan sebagainya. Perbedaan di kalangan para Sahabat ini telah melahirkan kecenderungan pemikiran yang berbeda di antara mereka baik mereka yang tergolong dalam kelompok ahl athar atau ahl ra’i. Perbedan yang jelas terjadi adalah kecenderungan pemikiran berasaskan terhadap maqasidi yang diwarnai oleh ijtihad Umar sedangkan kecenderungan pemikiran berasaskan terhadap syakli (formalisme) lebih jelas terlihat pada fiqh Abdullah Ibn Umar dan aliran-aliran ini merupakan aliran yang dibentuk berdasarkan kepada mashâdir hukum yang digunakan oleh setiap kelompok dalam melakukan istinbath hukum. Seorang fuqaha yang senantiasa melihat secara objektif Syariat Islam dalam melakukan istinbath hukum disebut sebagai Maqâsidi. Sedangkan fuqaha yang senantiasa melihat kepada rupa bentuk atau format dalam beristinbat hukum disebut sebagai Syakli. Oleh karena itu, dalam artikel ini ini penulis terdorong untuk mengkaji dan menganalisis pemikiran para fuqaha terhadap metodologi hukum berasaskan aliran maqasidi dan juga syakli.